2021
DOI: 10.1016/s2589-7500(21)00056-x
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning to detect acute respiratory distress syndrome on chest radiographs: a retrospective study with external validation

Abstract: Background Acute respiratory distress syndrome (ARDS) is a common, but under-recognised, critical illness syndrome associated with high mortality. An important factor in its under-recognition is the variability in chest radiograph interpretation for ARDS. We sought to train a deep convolutional neural network (CNN) to detect ARDS findings on chest radiographs. Methods CNNs were pretrained on 595 506 radiographs from two centres to identify common chest findings (eg, opacity and effusion), and then trained on 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 25 publications
0
44
0
Order By: Relevance
“…AI diagnostic models using biomedical imaging are increasingly being investigated to improve diagnostic accuracy and minimize the workload of radiologists. They are used to facilitate imaging diagnosis for simple tasks and have been successfully used for several disease processes, including COVID-19 [ 50 ], acute respiratory distress syndrome [ 51 ], and pneumothorax [ 52 ] detection. We envision using a similar model for rib fracture detection.…”
Section: Discussionmentioning
confidence: 99%
“…AI diagnostic models using biomedical imaging are increasingly being investigated to improve diagnostic accuracy and minimize the workload of radiologists. They are used to facilitate imaging diagnosis for simple tasks and have been successfully used for several disease processes, including COVID-19 [ 50 ], acute respiratory distress syndrome [ 51 ], and pneumothorax [ 52 ] detection. We envision using a similar model for rib fracture detection.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous studies using a similar model framework, they developed the ARDS classification model using 8073 CXRs as a training dataset and performed an excellent AUC (0.92, 95% CI 0.89–0.94). 14 Moreover, the results of Venn diagram indicated that there are some differences between the pattern of the clinical data classifier and the CNN model. Importantly, the combined machine learning model aims to provide related clinical and CXR information to identify ARDS for clinicians, which could result in shorter time to diagnosis and treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…In the fine-tuning step, we only retrained the parameters in the last convolutional block and subsequent layers to detect ARDS, while all the others were kept fixed after the pre-training. 14 Binary cross-entropy loss was used when adjusting model weights during training. The adaptive moment estimation (ADAM) optimizer was used to optimize the parameters of model training.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…image recognition, tumor identification, respiratory syndrome differentiation, etc. [ 4 6 ] Smartphone apps and other mHealth technologies have also been introduced as screening and monitoring tools for a wide range of ailments, including eye health, mental health, and a range of chronic diseases [ 7 9 ]. As such, digital health technology is playing an increasingly important role in clinical practice.…”
Section: Introductionmentioning
confidence: 99%